Silent cerebral lesions after catheter ablation for atrial fibrillation using cryoballoon, hotballoon, laserballoon and radiofrequency catheters: a Bayesian network meta-analysis - Zheng, Tiantian; Kong, Youjin; Wu, Li; Wu, Chenxia; Mao, Wei; Zhou, Xinbin (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCatheter ablation (CA) is an effective therapeutic option for patients with symptomatic atrial fibrillation (AF). Previous studies have reported silent cerebral lesions (SCLs) detected by magnetic resonance imaging (MRI) after different CA techniques; however, the results were controversial. Therefore, we performed this network meta-analysis (NMA) to assess the incidence of SCLs after cryoballoon, hotballoon, laserballoon, and radiofrequency ablation (RFA).MethodsDatabases such as PubMed, Embase, and the Cochrane Library were searched systematically. Both pairwise meta-analysis (PMA) and NMA were conducted. The primary outcome was the incidence of new SCLs on MRI after CA procedures.ResultsNine studies were analyzed and 1,057 patients were enrolled. Laserballoon ablation (LBA) had a higher incidence of SCLs than cryoballoon ablation (CBA) [odds ratio [OR] = 1.86, 95% confidence interval [CI] 1.06–3.27, p = 0.032] in the PMA, while no significant difference was detected between the CA techniques according to the NMA. The surface under the cumulative ranking curve (SUCRA) values indicated that CBA may be the best therapeutic option (SUCRA = 81.1%). The NMA results demonstrated similar procedure-related complication rates and mean activated clotting time between CBA (SUCRA = 53.7%, 66.3%), hotballoon ablation (HBA) (SUCRA = 81.5%, 43.6%), LBA (SUCRA = 3.39%, 42.8%) and RFA (SUCRA = 61.3%, 47.3%). LBA therapy required significantly more procedure time than CBA [weighted mean difference (WMD) = 24.36 min, 95% CI 12.51–36.21 min, p = 0.00].ConclusionsCBA treatment had lower incidence of post-procedural SCLs and took less procedure time compared with LBA for patients with AF. The procedure-related complications were comparable between CBA, LBA, HBA and RFA.Systematic Review RegistrationPROSPERO, identifier (CRD42024511110).